ANALISIS RESOURCE BASED VIEW USAHA PENGOLAHAN KOPI “UD. TYYANA COFFEE” DALAM MENCAPAI SUSTAINABLE COMPETITIVE ADVANTAGE - Tanjung, Yulia Windi (Jurnal Bisnis Tani, 2023)
Coffee is an export commodity as a source of foreign exchange, regional economic development and farmers’s income. UD. Tyyana Coffee is a coffee agribusiness Micro Small and Medium Enterprises. The aim of this study was to analyze the Resource Based View coffee processing business “UD. Tyyana Coffee” in achieving sustainable competitive advantage. Research methods are qualitative descriptive. Data analysis method uses a Resource Based View approach with the VRIO framework. The results of the study found that UD. Tyyana Coffee has the sustainable competitive advantage. Tangible resource in UD. Tyyana Coffee is ten resource that are sustaibanle competitive advantage, two resources are temporary competitive advantage, one resource is competitive parity, and two resources are competitive disadvantage. Intagible resources are fourteen resources are sustaibable competitive advantage and one resource is competitive disadvantage. While the results for the capabilities possessed are twelve capabilities are sustainable competitive advantage.